Uso, ocupação e erosão dos solos: um estudo sobre erosão laminar na bacia hidrográfica do ribeirão Douradinho, no Triângulo Mineiro - Silva, João Victor Freitas (2021)
Soil erosion has been considered as one of the most important environmental problems today. Although it occurs naturally, erosion tends to be accelerated as man, seeking to meet his needs and the demands turned to economic interests, changes the characteristics present in the environment. In recent decades, this accelerated erosion has been a cause for concern and aroused the interest of scientists and researchers. The causes that lead to its origin, evolution and, mainly, the search for its control have become the target of studies in several areas of knowledge. With this in mind, the present master's dissertation presents the results of an assessment of the susceptibility and potential to laminar erosion in the Douradinho stream basin in view of the natural environmental dynamics and economic interference, indicating the places most subject to the intensification of erosion and contributing to guide land occupation. The basin in question is located in the Intermediate Geographic Region of Uberlândia and is configured as a dynamic area with multiple uses. As a result, there is a need for the development of studies that enable the planning of land use with a view to the rational use and conservation of soils. For that, preliminary studies and the characterization of the physiographic aspects of the area in question were carried out. This characterization consisted, basically, in a segmented analysis and in the cartographic representation of the components referring to lithology, relief, soils, hydrography, climate and the use of the basin's soil, which are fundamental for the assessment of erosion in the place. The results showed that 64.79% of the land in the studied area are between the classes of moderate to very susceptible to the removal and transport of surface particles, thus corresponding to soils with high vulnerability in relation to the development of erosive processes, and that 46 , 11% of the total area of the basin has a current land use incompatible with the degree of susceptibility, falling between the classes of medium and high erosive potential, showing the places where adjustments are necessary in terms of land use / soil management and the application of appropriate conservationist practices. The data presented here may serve as a subsidy for the environmental planning of the basin.